2017
DOI: 10.1021/acs.energyfuels.6b02897
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Crude Oil Interfacial Material Isolated by the Wet Silica Method. Part 2: Dilatational and Shear Interfacial Properties

Abstract: To better understand the water-in-oil (w/o) emulsion stability problem, the interfacial material (IM) of four different crude oils was isolated using the wet silica method and analyzed by different techniques. In part 1 (10.1021/ acs.energyfuels.6b02899), we used gel permeation chromatography to analyze the molecular size distribution of S-, Ni-, and Vcontaining compounds. Here, we report the use of dilatational and shear interfacial rheology to analyze the interfacial properties of the IM films. In the second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…As expected for all systems that cross the gel point (such as bulk cross-linking polymers or physical gels), G becomes measurable after a while and increases with time with no apparent stabilization. Examples are given in ref . But even in this case (when G ≠ 0), gel-point rheology is observed for dilatational measurements made at low frequencies, , indicating that the interface has evolved to a state not too distant from the gel point, as expected for colloidal aggregation.…”
Section: About the Arguments Developed In Reference Against Interfac...mentioning
confidence: 80%
“…As expected for all systems that cross the gel point (such as bulk cross-linking polymers or physical gels), G becomes measurable after a while and increases with time with no apparent stabilization. Examples are given in ref . But even in this case (when G ≠ 0), gel-point rheology is observed for dilatational measurements made at low frequencies, , indicating that the interface has evolved to a state not too distant from the gel point, as expected for colloidal aggregation.…”
Section: About the Arguments Developed In Reference Against Interfac...mentioning
confidence: 80%
“…The abundance of polar groups in IM promoted hydrogen bonding, acid–base, dipole–dipole, and other van der Waals interactions. ,,, As a result, molecules were able to aggregate once adsorbed at the o/w interface and form a gelled network responsible for emulsion stability . Molecular simulations using archipelago-type model molecules revealed that the association of their sulfoxide groups rather than their aromaticity yields to the formation of the porous networks observed at the interface .…”
Section: Introductionmentioning
confidence: 99%
“…9,12,13,18 As a result, molecules were able to aggregate once adsorbed at the o/w interface and form a gelled network responsible for emulsion stability. 20 Molecular simulations using archipelago-type model molecules revealed that the association of their sulfoxide groups rather than their aromaticity yields to the formation of the porous networks observed at the interface. 18 On the contrary, continental-type molecules tend to self-assemble into ordered structures through parallel stacking, perpendicular to the water surface.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, emulsified water increases the crude oil volume and is strictly regulated, increasing the cost of transportation and refinement. Natural surfactants like asphaltenes, resins, and fine particles in the crude oil adsorb at water–oil interfaces and stabilize emulsions, introducing difficulties for demulsification. Of these, asphaltenes are believed to have the largest effect on emulsion stability. , …”
Section: Introductionmentioning
confidence: 99%